D-Planting pot / Harresh Ramesh Kumar ... [et al.] - Ramesh Kumar, Harresh; Md Noor, Muhammad Fakhrul Razzi; Ong, Song Wei; Tan, Lai Heng; Khoo, Kaa Hong; Ong, Song Li (2020)
Labis and Segamat area is popular with the king of fruit, durian. Residents around the area will usually throw the durian peel beside the road or farm. This evenly will have the effect of breeding flies and dengue mosquitoes. The process of decay for durian peel will also release unpleasant odors and carbon dioxide gas into the environment. The aim of this innovation is to reduce the problem of throwing durian peel anywhere and reuse the durian peel. The name of this product is D-PLANTING POT. D-Planting Pot is a small pot that made from durian peel. Durian peel contains cellulose. The fibers found in durian peel are rough but suitable to make a pot. The method used to make D-PLANTING POT is semichemical pulp. All ingredients need to be made into pulp by refining, soaking, and grinding. The resulting pulp will be filtered to filter out excess water. Wet pulp will be pasted into a container. About RM 10.00 is required for an innovation project to build the filter. As a result of the innovation, the pulp is rough and can make pots. The pots produced are hard and are suitable for planting seeds. The pots produced are biodegradable. In conclusion, D-PLANTING POT can be made from durian peel and can replace poly bags during seed germination in daily life.